Microparticle increase in severe obesity: Not related to metabolic syndrome and unchanged after massive weight loss. (2nd July 2013) - Stepanian, Alain; Bourguignat, Laure; Hennou, Sabiha; Coupaye, Muriel; Hajage, David; Salomon, Laurence; Alessi, Marie‐Christine; Msika, Simon; de Prost, Dominique
Abstract : Objective: To clarify the relationships between circulating microparticles (MPs), leukocyte–platelet aggregates (LPAs), obesity, and metabolic abnormalities and evaluate the effect of losing weight on these parameters. Design and Methods: In 151 severely obese women and 60 lean controls, total MPs (annexin‐V positive), platelet (annexin V/CD41+) and endothelial (CD31+/CD41−) MPs, and LPAs using flow cytometry, and the presence of metabolic syndrome (MS) were assessed. The effect of weight loss was studied in 32 subjects after a 1 year follow‐up. Results: Total microparticle count, platelet MPs (PMPs) and endothelial MPs (EMPs), and neutrophil–platelet aggregates were significantly increased in obese subjects versus lean controls, independently of the MS. Within obese subjects, there was no significant difference between those having and those not having MS. MPs and LPA counts did not vary significantly in subjects who lost 25% of their excess weight. Conclusions: PMPs and EMPs, and LPAs are associated with obesity independently of metabolic abnormalities, but do not significantly change after massive weight loss. Further studies are needed to evaluate the prognostic significance of these observations, as beneficial effects of MPs are currently reported in addition to their initially described deleterious effects.